Aliança, chefia e regionalismo no Alto Xingu - Antonio Roberto Guerreiro Júnior (Journal de la Société des Américanistes)
Alliance, chieftaincy and regionalism in Upper Xingu. The sharing of a kinship system is one of the upper-xinguano political system’s central elements. But the ethnographic data on alliance in the Upper Xingu is very limited, having never been subjected to a detailed treatment, and little of it could be appropriated by the most recent developments of South-American ethnology. In this article I present some data on alliance among the Kalapalo, an upper-xinguano carib-speaking group, and explore the recurrence among them of the ideal and practice of matrilateral marriage by chiefs, which coexists with a structure of inclusive restricted exchange. We will see that it is a structure in which chiefs’ alliance regime is doubly linked to hierarchy within the local group and to affinity relations between chiefs from different villages, which makes it possible to think about roles played by alliance and chieftaincy in the regional system of the Upper Xingu.